PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAM ACHIEVEMENT DIVISION (STAD) BERBANTUAN MEDIA INTERNET TERHADAP HASIL BELAJAR KOGNITIF PESERTA DIDIK KELAS XI IPA SMA NEGERI 2 MANOKWARI PADA MATERI LARUTAN PENYANGGA - Ade Rian; Yunita Pare Rombe; Apriani Sulu Parubak; Christiana Niken Larasati (Universitas Papua, Manokwari, Indonesia, 2019)
This study aims to determine: (i) the significant differences between the use of the STAD type cooperative learning model and the conventional learning model on students' cognitive achievement; (ii) measuring the percent effect of the two models carried out. This study uses a quasi-experimental design research method with a pretest posttest design. Mechanical sampling was done by purposive sampling. The instrument used to measure students' cognitive achievement is a multiple choice test. The data analysis used was descriptive and interferential analysis using SPSS 22 software. The results showed that there was no difference in cognitive learning outcomes in the Internet-Based Student Team Achievement Division (STAD) Cooperative Learning Model on Cognitive Learning Outcomes of students with this learning model. conventional.Keywords: STAD, Significant Difference, Cognitive, Percent Influence, Quasi Experiment